How patronage and clientelism works in village head elections in Karawang Regency, Indonesia? - Atthahara, Haura; Rizki, Mochamad Faizal; Nayiroh, Luluatu; Saputro, Nurcahyo Widyodaru (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The implementation of democracy at the village level in Indonesia is institutionalized through direct village head elections. However, rather than strengthening democratic values, the 2021 simultaneous elections in Karawang Regency revealed persistent patronage and clientelism. This study investigates how such practices undermine democratic consolidation by examining three villages with distinct socio-economic contexts: an agricultural village (K), a coastal village (C), and an industrial village (M). Using a case study approach, the research highlights the prevalence of money politics, including vote buying, distribution of goods, provision of services, and project-based patronage. Findings demonstrate that electoral competition was shaped not only by material inducements but also by personalized candidate–voter relationships, reinforcing clientelist ties. The urgency of this study lies in exposing how entrenched local political practices threaten the credibility of democratic institutions and village governance. The novelty of this research is its comparative analysis across villages with different economic bases, revealing context-specific patterns of patronage. The study contributes to debates on local democracy by showing that institutional reforms alone are insufficient without addressing the socio-political structures that perpetuate patronage and clientelism.